Peculiarities of bacteriosis development in agrocenosis of pome fruit orchards - Krym, I. (Interdepartmental Thematic Scientific Collection of Phytosanitary safety, 2024)
Goal. Was to determine ssources of bacterium diseases of pome fruits in agrocenoses and their seasonal development study and factors, which impacts on plants defeating level.Methods. Field (route, selective and continuous studies) and laboratory (extracting pure bacterium cultures, determining pathogenicity, identifying through the sum of morpho-cultural and their physiological and biochemical features).Results. There were determined the defeating peculiarities of pome fruits by bacteriosis defeating on pome fruits during the investigation in 2011—2015 and 2021—2023. Their causative agents was conformed by bacterium extraction from plant material. The most intensive bacterial necrosis happened in spring, during the period of juice intensive movement, when the tree is the most favorable to defeating. The defeating observed only on some shoots in summer (to 5% from the volume of tree crown), but the cancer development continued on the trunk’s bark. The first symptoms of fire blight observed during blossoming and at the beginning of fruit setting. The full picture opened during the shoots’ active growth. The shoots` defeating level was in the scope of 3—12% and only on some trees reached 15—18%. The fire blight strong defeat (to 55% of crown tree) observed in 2015 through the mass propagation pear-tree psylla. New fire blight sources were not identified in Chernivtsi region in 2021—2023.There were only presence of bacterial necrosis causative agent.Conclusions. The bacteriosis defeating determined and researched in plantations Chernivtsi and Vinnytsia regions. The highest fire blight defeating level (to 55% of crown) connected with mass propagations of pear-tree psylla. It is the main pathogen carrier. The bacterium necroses defeating depends upon the weather conditions of weather period and following the necessary level of agrotechnical measures. The investigation scheme for pome fruits bacteriosis determined developed with phenological phases terms considerations and periods of the most plants susceptibility to phytopathogens defeating.